Epidemiologie und Anatomie der Myopie - Jonas, Jost B.; Panda-Jonas, Songhomitra (Der Ophthalmologe, 2019)
BackgroundThe prevalence of myopia has markedly increased, particularly in the young generations in East and Southeast Asia.ObjectiveThe aim is to describe the epidemiology of myopia and the morphological alterations associated with myopia.Material and methodsThe results of epidemiological, clinical and histological studies are summarized.ResultsDuring the last three decades the prevalence of myopia has markedly increased so that currently 80-90% of 18-years-olds in East Asia are myopic and 10-20% are highly myopic. It is estimated that by 2050 the frequency of myopia worldwide will increase to 50% and high myopia to ca. 10% and high myopia will become the most frequent cause of irreversible blindness due to the association with myopic maculopathy and glaucomatous optic nerve atrophy. Myopia is morphologically characterized by predominantly sagittal and to a lesser extent coronal enlargement of the eyeball. This results in retinal thinning and reduction in the density of the retinal pigment epithelium (RPE) in the equatorial region, thinning of the choroid and sclera mostly at the posterior pole, normal retinal thickness and RPE density in the macular region, normal thickness of Bruch’s membrane (BM) in any region, elongated disc-fovea distance due to the development of parapapillary gamma and delta zones, enlargement and vertical rotation of the optic disc and elongation and thinning of the lamina cribrosa and peripapillary scleral flange.DiscussionThese morphological alterations can possibly be explained by a new formation and elongation of the BM in the equatorial region leading to sagittal elongation of the eyeball.